Muslim Responses to the COVID-19 Pandemic in Western Sydney: Understanding the Role of Community-Specific Communication Infrastructure. (2nd November 2022) - Mamalipurath, Jasbeer Musthafa; Notley, Tanya
ABSTRACT: In Australia, the COVID-19 pandemic rendered visible and exacerbated socio-economic inequalities and divides. Migrant and religious minority communities in Australia faced particular challenges during the pandemic when government responses were not made culturally accessible, appropriate or relatable. This paper examines the role played by community-specific communication infrastructures in addressing government deficiencies to meet the needs of Muslim communities. Drawing on semi-structured interviews with Muslims in an area hit hard by the pandemic – Western Sydney – we consider the role communication infrastructures played in combatting misinformation, providing up-to-date information and creating spaces for locally and culturally informed responses to be developed. We propose that community-specific communication infrastructures were critical to Muslims seeking to address gaps, needs and inequalities during the pandemic and they were effective because they were designed with an understanding of Muslim communities' social and cultural norms, practices, experiences and needs. The research offers insights relevant to migrant and religious communities, not-for-profits, and government agencies seeking to develop effective strategies to respond to challenges and crises as they emerge.